2011
DOI: 10.1063/1.3589860
|View full text |Cite
|
Sign up to set email alerts
|

Communication: New insight into the barrier governing CO2 formation from OH + CO

Abstract: Despite its relative simplicity, the role of tunneling in the reaction OH + CO → H + CO2 has eluded the quantitative predictive powers of theoretical reaction dynamics. In this study a one-dimensional effective barrier to the formation of H + CO2 from the HOCO intermediate is directly extracted from dissociative photodetachment experiments on HOCO and DOCO. Comparison of this barrier to a computed minimum-energy barrier shows that tunneling deviates significantly from the calculated minimum-energy pathway, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 34 publications
(32 reference statements)
3
51
0
Order By: Relevance
“…Botschwina and Oswald 16 built on previous work by Aoki 17 to generate highly accurate spectroscopic data for the microwave-range detection of C 5 N − by Cernicharo and co-workers 18 where corresponding laboratory data were not available. Further, computational tools have been utilized by Yu, Francisco, and co-workers [19][20][21][22][23][24][25][26][27][28][29][30][31][32] to better characterize the HOCO formation process, but there is still much that is uncertain, including accurate rovibrational spectroscopic constants and several of the fundamental vibrational frequencies. Huang, Lee, and co-workers [33][34][35][36][37] have predicted the fundamental vibrational frequencies of various molecular species to within a few cm −1 using advanced quantum chemical approaches which, further demonstrate the potential role of quantum chemistry in accurately examining difficult molecules often found in the conditions of interstellar space and extraterrestrial atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Botschwina and Oswald 16 built on previous work by Aoki 17 to generate highly accurate spectroscopic data for the microwave-range detection of C 5 N − by Cernicharo and co-workers 18 where corresponding laboratory data were not available. Further, computational tools have been utilized by Yu, Francisco, and co-workers [19][20][21][22][23][24][25][26][27][28][29][30][31][32] to better characterize the HOCO formation process, but there is still much that is uncertain, including accurate rovibrational spectroscopic constants and several of the fundamental vibrational frequencies. Huang, Lee, and co-workers [33][34][35][36][37] have predicted the fundamental vibrational frequencies of various molecular species to within a few cm −1 using advanced quantum chemical approaches which, further demonstrate the potential role of quantum chemistry in accurately examining difficult molecules often found in the conditions of interstellar space and extraterrestrial atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…The MEP from the cis-HOCO minimum to the H + CO 2 product asymptote is particularly relevant to HOCO − photodetachment since this is where strong tunneling was found. 12,13 The failure in re- producing the tunneling by a recent wave packet simulation 42 of the photodetachment experiment might be due to the thick barrier in the LTSH PES. The tunneling near TS2 may also be important 43 for the weak temperature dependence of the rate constant at low temperatures 4 and for the observed H/D kinetic isotope effect in the title reaction.…”
mentioning
confidence: 99%
“…In addition, significant tunneling towards H + CO 2 has been observed in photodetachment of the HOCO − anion. [11][12][13] Many theoretical studies of the reaction dynamics have been reported for the title reaction, using both quasi-classical trajectory (QCT) and quantum mechanical approaches. [14][15][16] However, the calculated rate constants at the low-pressure limit have been found to agree with experimental data only qualitatively.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, a new approach involving photoelectron-photofragment coincidence (PPC) measurements starting from the H(D)OCO − anion has become available. [14][15][16] In these experiments, the unimolecular decay of a neutral H(D)OCO radical by tunneling to H(D) + CO 2 can be directly observed. Of course all the thermal kinetics measurements have contributions of tunneling in them but there is no definitive way from only the measurements themselves to isolate and characterize the tunneling contribution.…”
Section: Introductionmentioning
confidence: 97%